2016
DOI: 10.1186/s13058-016-0754-9
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the mammary gland and mammary tumours in 3D: optical tissue clearing and immunofluorescence methods

Abstract: BackgroundHigh-resolution 3D imaging of intact tissue facilitates cellular and subcellular analyses of complex structures within their native environment. However, difficulties associated with immunolabelling and imaging fluorescent proteins deep within whole organs have restricted their applications to thin sections or processed tissue preparations, precluding comprehensive and rapid 3D visualisation. Several tissue clearing methods have been established to circumvent issues associated with depth of imaging i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 38 publications
1
100
0
Order By: Relevance
“…However, in veterinary species, welfare considerations are paramount, and this approach may be prohibited because of the use of sedation in pregnant and lactating rabbits. An alternative methodology which would likely yield informative results is high-resolution three-dimensional imaging using tissue clearing, which has recently been described in the mouse mammary gland Lloyd-Lewis et al 2016). A potential strength of our report is that the rabbits were wild and so no impact of artificial husbandry in a farm or laboratory environment is likely.…”
Section: Discussionmentioning
confidence: 90%
“…However, in veterinary species, welfare considerations are paramount, and this approach may be prohibited because of the use of sedation in pregnant and lactating rabbits. An alternative methodology which would likely yield informative results is high-resolution three-dimensional imaging using tissue clearing, which has recently been described in the mouse mammary gland Lloyd-Lewis et al 2016). A potential strength of our report is that the rabbits were wild and so no impact of artificial husbandry in a farm or laboratory environment is likely.…”
Section: Discussionmentioning
confidence: 90%
“…Lacrimal and epididymal tissue was dissected and fixed in NBF for 4-7 h. Pre-stimulation with OT [85 nM (lacrimal and mammary), 850 nM (epididymis), 5-20 min] was performed on live tissue prior to fixation, as indicated. Tissue clearing was performed on fixed tissue using a modified CUBIC protocol (15, 36). Briefly, tissue was immersed in CUBIC Reagent 1A [urea (10% w/w), Quadrol® (5% w/w), triton X-100 (10% w/w), NaCl (25 mM) in distilled water] for 2-3 days at 37°C, washed in PBS and blocked overnight at 4°C in PBS containing normal goat serum (10%) and triton X-100 (0.5%).…”
Section: Methodsmentioning
confidence: 99%
“…S1). GCaMP6f consists of a circularly permuted green fluorescent protein (GFP), enabling 3D assessment of its expression and lineage-specific localization using an anti-GFP antibody (14) and optimized methods for tissue clearing (15). Genetic recombination in this model was high (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…However, a recent report showed that the enzymatic digestion method used to prepare mammary ducts for 3D imaging can deplete myoepithelial cells and cause structural damage to ducts, and potentially might also deplete rare bi-lineage clones 20 . New methods of micro-dissection or clearing, together with whole-organ 3D imaging analysis and mathematical modeling 8, 12, 13, 2123 , will undoubtedly provide a clearer picture of mammary gland cell fate during normal development.…”
Section: Mammary Epithelial Cells Have Limited Plasticity In Vivomentioning
confidence: 99%